Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/membranes8020021
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a Supported Liquid Membrane in the Enrichment and Determination of Cadmium from Complex Aqueous Samples

Abstract: A supported liquid membrane is developed for the separation of Cd from either high in salinity or acidity aqueous media. The membrane consisted of a durapore (polyvinylidene difluoride) polymeric support impregnated with a 0.5 M Aliquat 336 solution in decaline. The effect of carrier concentration, organic solvent and feed and receiving solutions on the metal permeability is studied. This system allows the effective transport of trace levels of Cd through the formation of CdCl42−, which is the predominant spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The transport process can be described by the reaction between the metal and the carrier (R 4 P + Cl − ) present in the PIM: n R 4 P + Cl − PIM + [CdCl n +2 ] n− (aq) → [(PR 4 ) n CdCl n +2 ] PIM + n Cl − (aq) where n can be one or two, and the subscripts aq and PIM denote the aqueous and membrane phases, respectively. It is worth mentioning that when Aliquat 336 is used as the extractant, it has been reported that CdCl 4 2− species are responsible for the extraction in non-viscous media [ 3 ], whereas CdCl 3 − species are responsible for the extraction when viscous diluents are used [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport process can be described by the reaction between the metal and the carrier (R 4 P + Cl − ) present in the PIM: n R 4 P + Cl − PIM + [CdCl n +2 ] n− (aq) → [(PR 4 ) n CdCl n +2 ] PIM + n Cl − (aq) where n can be one or two, and the subscripts aq and PIM denote the aqueous and membrane phases, respectively. It is worth mentioning that when Aliquat 336 is used as the extractant, it has been reported that CdCl 4 2− species are responsible for the extraction in non-viscous media [ 3 ], whereas CdCl 3 − species are responsible for the extraction when viscous diluents are used [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The impregnated fiber was effective to preconcentrate Cd from seawater samples into a 1.5 M HNO 3 solution (used as a stripping phase). More recently, a supported liquid membrane (SLM) containing this IL was developed and studied in both flat-sheet and hollow fiber configurations to separate Cd from complex aqueous samples [ 3 ]. It was found that using a 2 M HCl solution containing Cd, Cu, Ni, and Pb as a feed phase, only Cd was transported.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low operating costs, minimal handling procedures, low energy requirement and low solvent consumption, the liquid membrane extraction (LME) process has been proposed as a more efficient and cost effective alternative to solvent extraction processes for the recovering REEs from coal y ash. [56][57][58] As the y ash materials need no pulverisation, and only a readily available acid (ethanoic acid) is required to extract the REEs, this process is potentially highly cost-effective. Compared to REE recovery via total acid digestion of y ash materials, the proposed process greatly reduces the toxicity of waste to be handled, which translates to lower cost.…”
Section: Implications Of Ree and Toxic Heavy Metals Fractionation For...mentioning
confidence: 99%
“…In SLM, a hydrophobic porous polymeric membrane holds the membrane liquid (membrane phase) into its micro-pores by capillary action. It has been proved that high viscosity (up to 500 cP) may slow down the displacement of the liquids from the micron pores under pressure and improve the SLM stability [25]. Aliquat 336 is used as a complex with counter ions (chlorides) to allow it to be dissolved in the hydrophobic organic phase (di-n-hexyl ether (DHE), a membrane diluent).…”
Section: Extraction Proceduresmentioning
confidence: 99%